2016
DOI: 10.1021/acs.organomet.6b00185
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of C–H Cyclopalladation at Tertiary Positions Enabled by an Exo-Directing Group

Abstract: Here we describe the first preparation of tertiary alkyl palladium complexes via C−H activation. Enabled by an exo-type oxime directing group, cyclopalladation occurred smoothly at the bridgehead position. Treatment of the resulting complex with iodine led to C−H iodination at the methine carbon. This study provides important mechanistic information for palladium-catalyzed functionalization of methine C−H bonds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 34 publications
0
10
0
1
Order By: Relevance
“…In contrast, transition-metal-catalyzed activation of tertiary CÀHb onds is rare.D ong and co-workers recently demonstrated that the Pd-catalyzed acetoxylation of tertiary CÀHb onds is possible at the bridgehead of bicyclo-[2.2.1]heptane (Scheme 72) [76,166] .Inaddition, it is noteworthy that the activation of the tertiary C À Hb onds of cyclopropanes [167] and cyclobutanes [168] has been achieved.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…In contrast, transition-metal-catalyzed activation of tertiary CÀHb onds is rare.D ong and co-workers recently demonstrated that the Pd-catalyzed acetoxylation of tertiary CÀHb onds is possible at the bridgehead of bicyclo-[2.2.1]heptane (Scheme 72) [76,166] .Inaddition, it is noteworthy that the activation of the tertiary C À Hb onds of cyclopropanes [167] and cyclobutanes [168] has been achieved.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Besides bidentate monoanionic auxiliaries, which can promote the activation of even some tertiary positions, [14] few directing groups can effect methylene C—H bond functionalization. We were pleased to discover that dimethylpyrazole directs the arylation of some secondary and even tertiary C—H bonds (Scheme 3).…”
mentioning
confidence: 99%
“…There have appeared reports in which either an imine or an oxime is used as an exo-directing group for C À Hb ond functionalization of primary amines. [12] Thus,w ee xamined various salicylaldehydes,w hich are sterically modified, as adirecting group for ap alladium-catalyzed CÀCb ond-forming reaction of primary amines.H erein, we report that arylation with an iodoarene successfully takes place to produce the corresponding g-arylated primary amine and ab uttressing salicylaldehyde [13] acts as the multipurpose,t hat is,e asily available, installable,r emovable,a nd recoverable,d irecting group for palladium. [11] We directed our attention to salicylaldehyde and its derivatives,which are readily available from commercial sources and easily synthesized and derivatized in al aboratory.T hey convert primary amines into the corresponding salicylaldimines,which are also called phenoxy-imines.U pon treatment with metals,s alicylaldimines chelate at the phenoxy group and the imino group, instantly in most cases,toform six-membered ring complexes.…”
mentioning
confidence: 99%
“…Once achelate complex is formed, the rigid backbone of the bidentate ligand places the metal in proximity of aspecific site of an amine for its activation. [12] Thus,w ee xamined various salicylaldehydes,w hich are sterically modified, as adirecting group for ap alladium-catalyzed CÀCb ond-forming reaction of primary amines.H erein, we report that arylation with an iodoarene successfully takes place to produce the corresponding g-arylated primary amine and ab uttressing salicylaldehyde [13] acts as the multipurpose,t hat is,e asily available, installable,r emovable,a nd recoverable,d irecting group for palladium. [14] Scheme 1.…”
mentioning
confidence: 99%